REVIEW OF THE EVENT OF DEFAULT IN REPURCHASE AGREEMENT TRANSACTIONS IN INDONESIA (CASE STUDY OF CENTRAL JAKARTA PN DECISION NUMBER 61/Pid.Sus-TPK/2020/PN Jkt.Pst AND SUPREME COURT RULING NUMBER 328 K/Pid.Sus/2022) - Caterin Caterin; Maya Nur Indah Sari (Jurnal Ilmiah Advokasi, 2024)
Referring to the Financial Services Authority Regulation Number 9/POJK.04/2015 concerning Guidelines for Repurchase Agreement Transactions for Financial Services Institutions, Repurchase Agreement contracts to sell or buy securities with promises to buy or resell at a predetermined time and price. In its implementation, the Global Master Repurchase Agreement becomes a standard that must be followed by the parties in making a Repo agreement. This journal uses a normative juridical method with descriptive writing specifications. The discussion in this journal is about Repo regulation in Indonesia in accordance with Financial Services Authority Regulation Number 9/POJK.04/2015 concerning Guidelines for Repurchase Agreement Transactions for Financial Services Institutions, particularly in terms of setting the event of default Repo.Keywords:  Event of default, Repurchase Agreement, Repo, and Global Master Repurchase Agreement